Question Number 49356 by peter frank last updated on 06/Dec/18
Commented by peter frank last updated on 07/Dec/18
$$\mathrm{am}\:\mathrm{getting}\:\mathrm{greatest}\:\mathrm{area}\:\mathrm{is}\:\:\mathrm{4}\pi\mathrm{a}. \\ $$
Answered by tanmay.chaudhury50@gmail.com last updated on 06/Dec/18
$$\left.\mathrm{2}\right){solve}\:{x}+{y}−\mathrm{1}=\mathrm{0} \\ $$$${y}^{\mathrm{2}} =\mathrm{6}{x} \\ $$$$\left(\mathrm{1}−{x}\right)^{\mathrm{2}} =\mathrm{6}{x} \\ $$$$\mathrm{1}−\mathrm{2}{x}+{x}^{\mathrm{2}} −\mathrm{6}{x}=\mathrm{0} \\ $$$${x}^{\mathrm{2}} −\mathrm{8}{x}+\mathrm{1}=\mathrm{0} \\ $$$${x}_{\mathrm{1}} +{x}_{\mathrm{2}} =−\left(−\mathrm{8}\right)=\mathrm{8} \\ $$$$\frac{{x}_{\mathrm{1}} +{x}_{\mathrm{2}} }{\mathrm{2}}=\mathrm{4} \\ $$$${y}=\mathrm{1}−{x} \\ $$$${y}_{\mathrm{1}} =\mathrm{1}−{x}_{\mathrm{1}} \\ $$$${y}_{\mathrm{2}} =\mathrm{1}−{x}_{\mathrm{2}} \\ $$$${y}_{\mathrm{1}} +{y}_{\mathrm{2}} =\mathrm{2}−\left({x}_{\mathrm{1}} +{x}_{\mathrm{2}} \right)=\mathrm{2}−\mathrm{8}=−\mathrm{6} \\ $$$$\frac{{y}_{\mathrm{1}} +{y}_{\mathrm{2}} }{\mathrm{2}}=−\mathrm{3} \\ $$$${so}\:{the}\:{midpoints}\:{of}\:{chords}\:\left(\mathrm{4},−\mathrm{3}\right) \\ $$